2016
DOI: 10.1177/0963721415628011
|View full text |Cite
|
Sign up to set email alerts
|

(Mis)Understanding Our Influence Over Others

Abstract: I review a burgeoning program of research examining people’s perceptions of their influence over others. This research demonstrates that people are overly pessimistic about their ability to get others to comply with their requests. Participants in our studies have asked more than 14,000 strangers a variety of requests. We find that participants underestimate the likelihood that the people they approach will comply with their requests. This error is robust (it persists across various samples and requests) and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 25 publications
0
26
1
Order By: Relevance
“…Furthermore, politeness may also decrease the likelihood of a donation because it makes it easier to say no, rather than 'giving in' to social pressure (Flynn & Lake, 2008;Bohns, 2016). This may be especially true for face-to-face encounters, though, which are not the focus of the current article.…”
Section: Politeness Hurts While the Politeness Helps Hypothesis Is Pmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, politeness may also decrease the likelihood of a donation because it makes it easier to say no, rather than 'giving in' to social pressure (Flynn & Lake, 2008;Bohns, 2016). This may be especially true for face-to-face encounters, though, which are not the focus of the current article.…”
Section: Politeness Hurts While the Politeness Helps Hypothesis Is Pmentioning
confidence: 98%
“…Polite requests show consideration for the feelings of listeners, and treat them as autonomous by showing that the decision is theirs to make. In daily life, we tend to avoid directives in favor of more polite requests (Holtgraves & Yang, 1990), and for a good reason: we believe that polite requests are more likely to be granted than requests phrased as directives (Bohns, 2016).…”
mentioning
confidence: 99%
“…Particularly, we showed that inexpressiveness, with either blank faces or untimely facial expressions, mitigates the face effect in the “sending” stage. This increases our understanding from the perspective of requesters (e.g., nonprofit organizations, service staff, and salespeople), which is largely neglected in the social influence research (Bohns, 2016). Therefore, our findings provide important insights into the burgeoning research of individual perceptions of their social influence on others (Roghanizad and Bohns, 2017), as well as present valuable contributions to studies on individual compliance, facial expressions, and communications.…”
Section: Discussionmentioning
confidence: 99%
“…Bohns (2016) suggests that awkwardness from saying no to requests drives many compliance decisions. In fact, social influence can occur even when others are anticipated to be present, not physically present, and imagined or anticipated social disapproval drives this effect (Modigliani, 1971).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…It is hard to imagine what we ourselves would feel and do in a given situation, let alone what another person with different motives, life experiences, and beliefs is likely to feel and do (Epley, Keysar, Van Boven, & Gilovich, 2004;Van Boven & Loewenstein, 2003;Van Boven, Loewenstein, & Dunning, 2005;Van Boven, Loewenstein, Dunning, & Nordgren, 2013). One consequence of these challenges of perspective-taking is that people consistently find it difficult to appreciate how hard it is for others to say "no" to social pressure (Bohns, 2016;Bohns et al, 2011;Bohns, Newark, & Xu, 2016;Bohns, Roghanizad, & Xu, 2014;Flynn & Lake (Bohns), 2008;Newark, Flynn, & Bohns, 2014). That is, people tend to underestimate the strong pressure others feel to avoid an awkward encounter and/or conform to social norms of agreement; as a result, people assume it is easier for someone to choose to do otherwise in a situation involving social influence than it actually is.…”
Section: The Effect Of Power On Beliefs About Responsibilitymentioning
confidence: 99%